The Representation of Prophetic Intelligence in The Learning Outcomes of Al-Islam and Kemuhammadiyahan - Bahar Agus Setiawan; Sofyan Rofi; Tri Endang Jatmikowati (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2022)
This study examines the learning outcomes of Al-Islam and Kemuhammadiyah in students, which can be related to the image of prophetic intelligence as an indicator. The paradigm of prophetic intelligence is closely related to the dimensions of intelligence. It can be understood as a continuation of the meaning of intelligence initially based on intellectual, emotional, spiritual, and collaboration into ESQ to prophetic intelligence. This perspective is closely related to the ideal desire that the purpose of education is not only intellectually intelligent but also emotional and spiritual and is currently popular with the term prophetic intelligence as an identity attached to the output produced. The balance of human/social dimensions with divine/religious dimensions is an inherent characteristic of the terminology of prophetic intelligence. This study aims to link the learning outcomes of Al-Islam and Muhammadiyah as an image of prophetic intelligence to students as ordinary people. The basis of the research method used refers to a qualitative approach with research instruments in the form of a questionnaire with structured answer options. The study found that Al-Islam and Kemuhammadiyahan learning can develop and improve on the human/social dimension, which includes tolerance, critical and creative attitudes, maturity in attitude, and communicativeness as an indicator of the image of prophetic intelligence that can be relied on several events in the life of the Prophet Muhammad such as Hudaibiyah agreement, laying of the Black Stone, and leadership in the state of Medina. As for the divine/religious dimension, the learning outcomes of Al-Islam and Muhammadiyah, such as faith, understanding of the Qur'an, and the totality of implementation of the halal-haram aspects, although they have improvements and results, cannot be pinned on the dimensions of prophetic intelligence, due to differences in the position of students as ordinary people.